PENGARUH POLA ASUH ORANG TUA PETANI KARET TERHADAP MINAT STUDI KE PERGURUAN TINGGI DI DESA PANGKAL NIUR, BANGKA - K, Angi Anggreani; Wilodati; Sartika, Rika (Jurnal Pendidikan Sosiologi Undiksha, 2024)
According to the latest data from the Central Bureau of Statistics in 2021, the interest rate for children in the Bangka Belitung Islands to enter college is low. The participation rate of children aged 19 years and over to go to college in Bangka Belitung is only 15.52 percent (Indarti et al., 2021). One of the factors that influence student interest is parents. This research was conducted in Pangkal Niur Village, Riau Silip Subdistrict, Bangka Regency, Bangka Belitung Islands due to the large number of children who should be at that age and based on the level of secondary education that has been completed previously who do not continue their education to college. This study aims to determine the effect of parenting patterns of rubber farmer parents on children's interest in studying at college in Pangkal Niur Village. The approach in this study is to use Quantitative with survey methods through questionnaires. The results revealed that in this study: first, based on 82 respondents, the dominant parenting pattern was 48% or 39 respondents received permissive parenting from their parents. Second, as many as 71% or 58 respondents have a fairly high level of interest in study. Third, that the parenting pattern of rubber farmer parents has an effect of 23% on the interest in continuing education to college in Pangkal Niur Village, Bangka.